THE POTENTIAL OF EPIDERMAL GROWTH FACTOR RECEPTOR MOLECULES AS PREDICTORS OF CLINICAL STAGE AND PROGNOSIS OF SQUAMOUS CELL CARCINOMA IN MEDAN CITY - Hasibuan, Ariq Muflih Halim; Pramesti, Tisya Amanah; Dwiyanti, Atika (Medicina Biomedica Journal, 2022)
Squamous cell carcinoma (SCC) is a non-melanoma skin malignant tumor originating from the suprabasal keratinocytes of the epidermis. Exposure to ultraviolet radiation is known to be one of the main triggers so that the place of predilection for this malignancy is an area that is often exposed to sunlight, especially the head and neck. Assessing the potential of the Epidermal Growth Factor Receptor (EGFR) molecule in predicting the clinical stage and prognosis of squamous cell carcinoma of the skin. This study used 40 samples of keratinized and non-keratinized Squamous Cell Carcinoma patients who were then given EGFR staining by immunohistochemistry. The result of staining on EGFR by immunohistochemistry is brown, whereas if it appears blue, the result is negative. The relationship of EGFR expression from 40 slides of SCC collected with EGFR immunohistochemical staining found 6 malignant tumors (15%) negative EGFR, then 14 malignant tumors (35%) showed weak grade (positive 1), 6 malignant tumors (15%) showed moderate expression level (positive 2) and 14 malignant tumors (35%) showed strong expression (positive 3). The test results showed a significant relationship between the level of EGFR with the clinical stage of squamous cell carcinoma as indicated by the value of p = 0.030 ( 0.05). The analysis was analyzed using the two-tailed Bivariate Correlation test. Expression of EGFR molecules on immunohistochemical staining of SCC of the skin can be used to determine the clinical stage of SCC of the skin.